Correction to: DElaying Disease Progression In COPD with Early Initiation of Dual Bronchodilator or Triple Inhaled PharmacoTherapy (DEPICT): A Predictive Modelling Approach (Advances in Therapy, (2023), 40, 10, (4282-4297), 10.1007/s12325-023-02583-1) - Singh, Dave; Litewka, Diego; Páramo, Rafael; Rendon, Adrian; Sayiner, Abdullah; Tanni, Suzana E. [UNESP]; Acharya, Sudeep; Aggarwal, Bhumika; Ismaila, Afisi S.; Sharma, Raj; Daley-Yates, Peter (Springer Nature, 2023)
In the original article, the superscript letters denoting the footnotes were missing. The correct figure is given below: (Figure presented.) The original article has been corrected.